A DRAO and VLA investigation of the environment of WR 130 - Cichowolski, Silvina (2001)
The environment of the Wolf-Rayet (WR) star WR 130 has been studied using the 21 cm H I line and radio continuum data at 408 and 1420 MHz obtained with the Dominion Radio Astrophysical Observatory (DRAO) Synthesis Telescope. In addition, the H110a recombination line and 21 cm H I line were observed using the Very Large Array in the DnC and D configurations.